Diese Seite drucken

Dreieckschaltung

Formeln der symmetrischen Dreieckschaltung

S_Dreieck = 3 * U_^2 / Z_*

S_Dreieck = IL^2 * Z_

S_Dreieck = √3 * UDreieck * IL <φ

 

UDreieck = |U12| = |U23| = |U31|

UDreieck = √3 * UStern

UDreieck = UStrang

 

IStrang = ILeiter / √3

IStrang = UDreieck / Z

IDreieck = IStrang

ILeiter = |I1| = |I2| = |I3|

ILeiter = IStrang * √3

 

Wirkleistung P = S_Dreieck * cos(φ)    (Einheit: VA)

Wirkleistung P = √3 * U_Dreieck * ILeiter * cos(φ)

 

Blindleistung Q = S_Dreieck * sin(φ)    (Einheit: var)

Blindleistung Q = √3 * U_Dreieck * ILeiter * sin(φ)

 

S_Dreieck = S_Stern = √3 * UDreieck * ILeiter < φ


Formeln der asymmetrischen Dreieckschaltung

 

Dreieckschaltung

UDreieck = UStrang = UStern * √3

 

IStrang = UStrang / Z = UDreieck / Z

ILeiter = IStrang * √3

 

In = 0

I1 = U1 / Z1

I2 = U2 / Z2

I3 = U3 / Z3

 

SDreieck = 3 * (S1 + S2 + S3)

SDreieck = 3 * (UDreieck² / ZGesamt)

SStrang = UStrang * IStrang^* = UDreieck² / ZGesamt = UStrang² / ZStrang

 

PDreieck = SDreieck * cos(φ)

PDreieck = √3 * UDreieck * ILeiter * cos(φ)

 

QDreieck = SDreieck * sin(φ)

QDreieck = √3 * UDreieck * ILeiter * cos(φ)